Strategies to eradicate bullying in secondary schools - Yahaya, Azizi; Ma'alip, Halimah (2004)
Bullying is a serious problem that can dramatically affect the ability of students to progress academically and socially. A comprehensive intervention and prevention plan that involves students, parents, and school staff is required to ensure that all students can learn in a safe and fear-free environment. The article offers to the schools and education authorities the various strategies to be adopted in halting the menace of bullying in secondary schools. The article also highlights those facts that bullying is more than just teasing and anyone can be a bully and a victim. As bullying affects everyone, therefore students, parents and school teachers can work together to find solutions with the best results.